Project studios in university education - E. V. Reshetnyak; A. A. Tarelin (Высшее образование в России)
This paper deals with project studios in university teaching and learning as mean of enhancement of practical value of students professional development. The authors describetheir expertise in applying such format for preparation of master level students of NTU“Kharkiv Polytechnic Institute” as well as define peculiarities of project studio format implementation and its advantages.